Facile luminescent tuning of ZnII/HgII complexes based on flexible, semi-rigid and rigid polydentate Schiff bases from blue to green to red: structural, photophysics, electrochemistry and theoretical calculations studies1. Issue 17 (7th May 2015) - Wang, Xin-Ming; Chen, Shuo; Fan, Rui-Qing; Zhang, Fu-Qiang; Yang, Yu-Lin
<x xml:space="preserve">Abstract</x> The photophysical properties of ZnII/HgII Schiff base complexes could be tuned by changing the ligand structures.